Idee Fryderyka Nietzschego w polskiej myśli o wychowaniu w latach 1883–1939 - Dworakowska, Katarzyna (Biuletyn Historii Wychowania, 2009)
The article discusses outstanding interpretations of the works by F. Nietzsche as represented in Polish educational thought during the “Young Poland” period and the following interwar period. The study aims at elucidating the pedagogical dimensions of Nietsche’s idea in the interpretation of the two periods and at identifying the space within which the concept of the author of Thus spake Zarathustra still remains topical and current. The section devoted to the “Young Poland” period includes an analysis of Jan Kurnatowski’s book Nietsche. Studia i tłumaczenia [Nietzsche. Studies and translations], the one and only work of the period that extracts from the output of the German thinker its strictly pedagogical reflections. The next issue to be presented is a discussion on the journalistic writing that was engaged inNietzschean themes that would be of interest to the present-day pedagogy of culture. Interpretation trends that aimed to discover a universal remedy for the crisis in culture and humanity in the works of the author of Untimely Meditations turned out to be dominant at the time. An approach to the interpretation of Nietzsche’s thought in a wide context of social and cultural interactions made it possible to conclude that the category of Bildungsphilister, castigated by the philosopher, reaches much further beyond just criticism of the contemporary model of education due to the tenability of the notion of Bildumg as the accumulation of cultural capital as it was viewed by Pierre Bourideu. In conclusion of the discussion on the modernist period, the author presents postulations that indicate a need for a shift in the reception emphasis towards directions hitherto unexplored. The section devoted to the interwar period presents the interpretation of the pedagogical thought of Nietzsche presented at the inauguration lecture (on the occasion of Antoni Bolesław Dobrowolski’s acceptance of the chair of pedagogy at Wolna Wszechnica Polska [Free Polish University]) delivered by the professor. The presentation is followed by a discussion on the different approaches presented in various pedagogical encyclopaedias and in Ludwik Chamaj’s Kieruki i prądy pedagogiki współczesnej [Trends and directions in modern pedagogy]. The latter approaches present Nietzsche as an instigator and a prime mover in contemporary intellectual currents and trends and discuss his influence upon individual philosophers, extracting from his philosophical output the notions of “individualism”, “criticism of the traditional educational system” and “irrationalism”. The journalistic writings under investigation fit well into this particular interpretative trend. The discussion on the interwar period is complemented with a reference to a booklet written by Stanisław Besser and entitled: Bohaterowie myśli. Nietsche i Weininger [Heroes of Thought. Nietzsche and Weininger] and an analysis of the article written by Marian Wachowski Wspomnienia z pism pedagogicznych Nietzschego i Grundtviga [Pedagogical reflections in the writings of Nietzsche and Grundtvig], being the only Polish contribution to the discussion on the series of lectures by Nietzsche Ueber die Zukunft unserer Bildungsanstalten